Factors predicting recanalization following stent-assisted coil embolization of unruptured intracranial aneurysms with long-term follow-up - Won, Yu Deok; Kim, Young Deok; Ban, Seung Pil; Kwon, O-Ki (Frontiers in Neurology, 2024)
Objective Stents have been widely used for coil embolization for intracranial aneurysms. Few studies have analyzed the risk factors of recanalization through long-term follow-up observation of only stent-assisted coiling. We analyzed the risk factors for recanalization through long-term observations. Methods A total number of 399 unruptured aneurysms treated by stent-assisted coil embolization between 2003 and 2016 in a single institution were analyzed for determining the factors associated with recanalization including the patient characteristics, aneurysms, and procedural variables. All patients underwent angiographic follow-up with digital subtraction angiography or magnetic resonance angiography at 24 months or more following the procedure. Results Recanalization occurred in 8%. The mean time for the recanalization was 21.1 ± 14.0 months (range, 5–51 months). The receiver operating characteristic curve analysis indicated areas under the curve for a maximum aneurysm size of 0.773 (cut-off, 6.415 mm). Multivariate analysis revealed that the maximum aneurysm size and parent artery curvature at which the aneurysm developed were significantly associated with recanalization. In parent artery curvature, the bifurcation group (OR, 9.02; 95% CI, 2.53–32.13; p = 0.001) and the convex group (OR, 3.68; 95% CI, 1.17–11.50; p = 0.025) were independent predictors of recanalization compared with the straight group. Conclusion The maximum aneurysm size and parent artery curvature are risk factors associated with recanalization in stent-assisted coil embolization.